Relationship of Self-Rated Health to Stroke Incidence and Mortality in Older Individuals with and without a History of Stroke: A Longitudinal Study of the MRC Cognitive Function and Ageing (CFAS) Population. - Nahal Mavaddat; Rianne van der Linde; Richard Parker; George Savva; Ann Louise Kinmonth; Carol Brayne; Jonathan Mant (PLoS ONE)
Introduction Poor self-rated health (SRH) has been associated with increased risk of death and poor health outcomes even after adjusting for confounders. However its' relationship with disease-specific mortality and morbidity has been less studied. SRH may also be particularly predictive of health outcomes in those with pre-existing conditions. We studied whether SRH predicts new stroke in older people who have never had a stroke, or a recurrence in those with a prior history of stroke. Methods MRC CFAS I is a multicentre cohort study of a population representative sample of people in their 65th year and older. A comprehensive interview at baseline included questions about presence of stroke, self-rated health and functional disability. Follow-up at 2 years included self-report of stroke and stroke death obtained from death certificates. Multiple logistical regression determined odds of stroke at 2 years adjusting for confounders including disability and health behaviours. Survival analysis was performed until June 2014 with follow-up for up to 13 years. Results 11,957 participants were included, of whom 11,181 (93.8%) had no history of stroke and 776 (6.2%) one or more previous strokes. Fewer with no history of stroke reported poor SRH than those with stroke (5 versus 21%). In those with no history of stroke, poor self-rated health predicted stroke incidence (OR 1.5 (1.1-1.9)), but not stroke mortality (OR 1.2 (0.8-1.9)) at 2 years nor for up to 13 years (OR 1.2(0.9-1.7)). In those with a history of stroke, self-rated health did not predict stroke incidence (OR 0.9(0.6-1.4)), stroke mortality (OR 1.1(0.5-2.5)), or survival (OR 1.1(0.6-2.1)). Conclusions Poor self-rated health predicts risk of stroke at 2 years but not stroke mortality among the older population without a previous history of stroke. SRH may be helpful in predicting who may be at risk of developing a stroke in the near future.